Decision Making in Peripheral Nerve Injury - Ferry Senjaya (Indoscholar, 2018)
The decision making process during diagnosis and treatment of a peripheral nerve injury can be complex at times. The nature and cause of nerve injury, its location, and its severity require very distinct decisions with regards to timing and intervention chosen. For good decision-making, a good knowledge of the pathophysiological conditions of peripheral nerve and its response to injury is paramount. In this article, the decision-making process related to pre-operative, intra-operative, and post-operative periods are discussed.